Caracterização de aços maraging livres de cobalto produzidos por metalurgia do pó - Pereira, Eduardo Emanuel de Lima (Universidade Federal Rural do Semi-Árido, 2019)
Maraging steels are very important and relevant materials as alternatives for the most diverse applications due to their combination of desired properties. However they are not cheap materials, and alternatives are sought to facilitate their obtaining. The aim of the present work was to obtain and characterize a series of maraging steels, and for that, analyzed samples of three types of different maraging steels belonging to the T series, being T-200, T-250 and T-300, which were produced by powder metallurgy. Techniques were used to characterize these samples, such as microscopy, microhardness test and x-ray diffraction. The results showed how the compression pressure and the sintering temperature influenced the porosity of the samples as well as their average hardness. The X-ray diffraction showed that the diffractograms of the samples were very similar, almost identical.
Monografia
Keywords: Aços Maraging; Caracterização; Propriedades; Maraging Steel; Characterize; Maraging Steel, Properties; ENGENHARIAS::ENGENHARIA MECANICA